Enhanced MRI-guided radiotherapy with gadolinium-based nanoparticles: preclinical evaluation with an MRI-linac - H. L. Byrne; G. Le Duc; F. Lux; O. Tillement; N. M. Holmes; A. James; U. Jelen; B. Dong; G. Liney; T. L. Roberts; Z. Kuncic (Cancer Nanotechnology, 2020)
Abstract Background The AGuIX® (NH TherAguix) nanoparticle has been developed to enhance radiotherapy treatment and provide strong MR contrast. These two properties have previously been investigated separately and progressed to clinical trial following a clinical workflow of separate MR imaging followed some time later by radiotherapy treatment. The recent development of MRI-linacs (combined Magnetic Resonance Imaging–linear accelerator systems enabling MRI-guided radiotherapy) opens up a new workflow where MR confirmation of nanoparticle uptake can be carried out at the time of treatment. A preclinical study was carried out to assess the suitability of a gadolinium-containing nanoparticle AGuIX® (NH TherAguix) for nano-enhanced image-guided radiotherapy on an MRI-linac. Methods Treatments were carried out on F344 Fischer rats bearing a 9L glioma brain tumour. Animals received either: (A) no treatment; (B) injection of nanoparticles followed by MRI; (C) radiotherapy with MRI; or (D) injection of nanoparticles followed by radiotherapy with MRI. Pre-clinical irradiations were carried out on the 1.0 T, 6 MV in-line Australian MRI-linac. Imaging used a custom head coil specially designed to minimise interference from the radiotherapy beam. Anaesthetised rats were not restrained during treatment but were monitored with a cine-MRI sequence. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis was used to quantify residual gadolinium in the brain in normal and tumour tissue. Results A preclinical evaluation of nano-enhanced radiation treatment has been carried out on a 1.0 T MRI-linac, establishing a workflow on these novel systems. Extension of life when combining radiotherapy with nanoparticles was not statistically different from that for rats receiving radiotherapy only. However, there was no detrimental effect for animals receiving nanoparticles and radiation treatment in the magnetic field compared with control branches. Cine-MR imaging was sufficient to carry out monitoring of anaesthetised animals during treatment. AGuIX nanoparticles demonstrated good positive contrast on the MRI-linac system allowing confirmation of tumour extent and nanoparticle uptake at the time of treatment. Conclusions Novel nano-enhanced radiotherapy with gadolinium-containing nanoparticles is ideally suited for implementation on an MRI-linac, allowing a workflow with time-of-treatment imaging. Live irradiations using this treatment workflow, carried out for the first time at the Australian MRI-linac, confirm the safety and feasibility of performing MRI-guided radiotherapy with AGuIX® nanoparticles. Follow-up studies are needed to demonstrate on an MRI-linac the radiation enhancement effects previously shown with conventional radiotherapy.